Advances in the green chemistry of coordination polymer materials. Issue 12 (26th May 2020) - Engel, Emile R.; Scott, Janet L.
Abstract : A perspective on the development of coordination polymers based on sustainable benign ligands and metals, and green synthesis. Abstract : Coordination polymers, including metal–organic frameworks, are a diverse class of materials with myriad properties and potential applications. However, a number of drawbacks have hindered the scaling up of such materials towards commercial applications. These include health and safety risks, environmental hazards, poor cost efficiency and sustainability shortfalls. In contrast to the systematic progress of organic green chemistry, which has contributed to improvements in the sustainability of chemical processing, the development of green chemistry in the context of coordination polymers has been fragmented and sporadic. This review describes advances in the use of green components: benign sustainable ligands and non-hazardous earth abundant metals. Additionally, solvent considerations, synthesis strategies for improved sustainability and the performance of coordination polymers relative to alternative competing materials are discussed.